Communities and Crime: An Enduring American Challenge - Wilcox, Pamela (Urban Life, Landscape and Policy Ser, 2017)
"Contents" -- "1. Images of Community in Criminological Thought" -- "2. Community as Socially Disorganized" -- "3. Community as a System" -- "4. Community as the Truly Disadvantaged" -- "5. Community as a Criminal Culture" -- "6. Community as a Broken Window" -- "7. Community as Criminal Opportunity" -- "8. Community as Collective Efficacy" -- "9. Communities and Crime: Looking Ahead" -- "References